Analysis of the Implemetation of Enterprise Resource Planning (ERP) SAP S/4 HANA in Cost Control of Light Rail Transit (LRT) Construction Projects - Zulkarnaini, Rizki; Kussumardianadewi, Bernadette Detty (CSID Journal of Infrastructure Development, 2026)
Construction projects are expensive, complex, and difficult to keep on budget. Cost overruns are common. The consequences, including delays, disputes, and financial losses, appear repeatedly across the sector. Enterprise Resource Planning (ERP) systems have been widely adopted to address this challenge, but evidence on how SAP S/4HANA performs in Light Rail Transit (LRT) construction is limited. This study analyzed the critical success factors of SAP S/4HANA implementation and evaluated its effect on cost control performance in an LRT project in Jakarta. Data were collected from two sources: a questionnaire distributed to 50 respondents involved in the project, and cost records extracted from SAP S/4HANA at project completion. All variables were validated through expert consultation before the main questionnaire was distributed. Three factors significantly affected cost control performance. SAP S/4HANA system quality (X1) was significant at sig. = 0.017 (t = 2.466). Organizational support (X2) was significant at sig. = 0.019 (t = 2.347). SAP S/4HANA users (X3) produced the strongest effect, significant at sig. = 0.000 (t = 4.708). The F-test confirmed that all three variables jointly affected cost control (F = 11.834, p < 0.05). User competence ranked first among the three factors, followed by system quality, then organizational support. The project recorded a Cost Planning value of Rp 4,665,465,828,436 against an Actual Cost of Rp 4,656,147,335,236. Earned Value across all four project zones reached Rp 4,915,100,000,000. The Cost Performance Index (CPI) was 1.055, indicating the project was completed within the planned budget. These findings extend ERP success research into transport infrastructure, where empirical evidence of this kind is scarce. Contractors deploying SAP S/4HANA on large construction projects should prioritize user training across the PS, MM, and FI modules before construction begins. On this project, the system provided real-time cost visibility and kept project spending within the planned budget.